Determination of diffusion lengths for intermixed quaternary quantum well with polarized edge-emitting photoluminescence - Xu, C. D. (2010)
Diffusion lengths of the group III and V sublattices are quantitatively determined for intermixing of a quaternary InGaAs/InP quantum well using polarized edge-emitting photoluminescence. Diffusion-length loci are plotted on a contour diagram of wavelength shifts of electron-heavy-hole and electron-light-hole transitions and illustrate the time progression of intermixing clearly. The plasma-enhanced intermixing effect is investigated using this technique, showing the difference of intermixing development in the early and the late stages. It is seen that the calculated diffusion-length ratio may change with the annealing duration.